'Embrace the masculine; attenuate the feminine': gender, identity work and entrepreneurial legitimation in the nascent context - Swail, Janine; Marlow, Susan (Taylor & Francis, 2017)
This paper critically analyses how gender bias impacts upon women’s efforts to legitimate nascent ventures. Given the importance of founder identity as a proxy for entrepreneurial legitimacy at nascency, we explore the identity work women undertake when seeking to claim legitimacy for their emerging ventures in a prevailing context of masculinity. In so doing, we challenge taken for granted norms pertaining to legitimacy and question the basis upon which that knowledge is claimed. In effect, debates regarding entrepreneurial legitimacy are presented as gender neutral yet, entrepreneurship is a gender biased activity. Thus, we argue it is essential to recognise how gendered assumptions impinge upon the quest for legitimacy. To illustrate our analysis, we use retrospective and real time empirical evidence evaluating legitimating strategies as they unfold, our findings reveal tensions between feminine identities such as ‘wife’ and ‘mother’ and those of the prototypical entrepreneur. This dissonance prompted women to undertake specific forms of identity work to bridge the gap between femininity, legitimacy and entrepreneurship. We conclude by arguing that the pursuit of entrepreneurial legitimacy during nascency is a gendered process which disadvantages women and has the potential to negatively impact upon the future prospects of their fledging ventures.